2019
DOI: 10.1016/j.metop.2019.100016
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammation markers in the prediction of weight gain and development of obesity in adults – A prospective study

Abstract: Background and aims There is a growing body of literature confirming the association between inflammation and obesity. Recent research suggests that inflammation may play a role in weight gain. The aim of the study was to analyse whether serum inflammatory markers predict weight gain or development of obesity in a prospective study design. Methods and results The baseline study (DILGOM 2007) consists of a population-based sample of 5024 Finnish men and women aged 25–75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
2
10
2
Order By: Relevance
“…CRP was not included in a US study with a 3-year follow-up of 45–64-year-old individuals ( n = 11,687), however, higher baseline levels of fibrinogen and leukocytes were associated with higher weight gain particularly among those who recently had quit smoking [ 26 ]. Our results do not confirm the findings from these two previous studies, but are in line with another Finnish study where smoking status did not affect the association between hs-CRP and weight change [ 34 ].…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…CRP was not included in a US study with a 3-year follow-up of 45–64-year-old individuals ( n = 11,687), however, higher baseline levels of fibrinogen and leukocytes were associated with higher weight gain particularly among those who recently had quit smoking [ 26 ]. Our results do not confirm the findings from these two previous studies, but are in line with another Finnish study where smoking status did not affect the association between hs-CRP and weight change [ 34 ].…”
Section: Discussioncontrasting
confidence: 91%
“…The few existing studies have reported similar and contradictory results to ours. The results of a Finnish population-based study on associations of several inflammation markers including hs-CRP with future weight gain (self-reported weight) during a 7-year follow-up among 25–75 years old adults ( n = 3369) are consistent with ours, such that no associations between hs-CRP and obesity indicators were observed after adjusting for baseline BMI [ 34 ]. On the contrary, in a study from the US ( n = 3254), higher baseline CRP concentration was associated with both weight loss and weight gain.…”
Section: Discussionsupporting
confidence: 67%
“…FINRISK 2007 participants who lived in Helsinki, Vantaa, Turku and Loimaa area were invited to a follow-up examination in 2014 (participation rate for health examination in 2014 54%) [ 7 , 8 ]. All living participants of Health 2000 were invited to participate in a follow-up examination in 2011 (participation rate for health examination 59%) [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, several studies have mentioned that inflammatory markers may be associated with weight gain, especially in middle-aged adults [ 57 ]. By contrast, some reports have noted a negative correlation between cytokine levels (IL-6, adiponectin, and TNF-α) and obesity [ 58 ], suggesting that inflammation is a consequence of obesity rather than a contributing factor [ 56 ].…”
Section: The Role Of Adipose Tissue In the Immune Responsementioning
confidence: 99%